2015
DOI: 10.1063/1.4928904
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radial and longitudinal force of plasma wakefield generated by a chirped pulse laser

Abstract: In present paper, the chirp effect of an electromagnetic pulse via an analytical model of wakefield generation is studied. Different types of chirps are employed in this study. Our results show that by the use of nonlinear chirped pulse the longitudinal wakefield and focusing force is stronger than that of linear chirped pulse. It is indicated that quadratic nonlinear chirped pulses are globally much efficient than periodic nonlinear chirped pulses. Our calculations also predict that in nonlinear chirped pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For instance, Rezaei-Pandari et al found that a properly chirped laser pulse could excite stronger laser wakefield in an inhomogeneous plasma, which could result in higher electron energy [25]. Ghasemi et al proved that the nonlinearly chirped laser pulse can generate stronger longitudinal wakefield and focusing force than that of the linearly chirped laser [26]. Zhang et al showed that a chirped laser pulse can greatly enhance the wakefield amplitude and potential regardless of chirp sign, which would affect the ionization-induced injection process [27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Rezaei-Pandari et al found that a properly chirped laser pulse could excite stronger laser wakefield in an inhomogeneous plasma, which could result in higher electron energy [25]. Ghasemi et al proved that the nonlinearly chirped laser pulse can generate stronger longitudinal wakefield and focusing force than that of the linearly chirped laser [26]. Zhang et al showed that a chirped laser pulse can greatly enhance the wakefield amplitude and potential regardless of chirp sign, which would affect the ionization-induced injection process [27].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of relativistic CLPs with underdense plasma can be described by the coupled equations under the Coulomb gauge [40,41,[48][49][50][51] :…”
Section: Mode and Schemementioning
confidence: 99%
“…where, n 0 =n(ξ=0) is the plasma density of the initial position, n(ξ) describes the inhomogeneity of the plasma density, which is a nonlinear function of ξ, and the specific expression will be given in the next section. Thus, the response of the plasma to the laser pulse can be described by the equation of motion in three directions [35,36]:…”
Section: Model and Analysismentioning
confidence: 99%
“…It is shown that the maximum amplitude of the wakefield induced by nonlinearly chirped pulse is three times longer than that by linearly chirped pulse. And the effect of various types of chirped pulse on wakefield generation by a rationally analytical model is given [36].…”
Section: Introductionmentioning
confidence: 99%